Nickel-based single-crystal high-temperature alloy and component design method and preparation method thereof

By optimizing the alloy composition and heat treatment process, the size and stability of the γ′ phase were controlled, solving the problem of high strength and high microstructure stability of nickel-based single crystal high-temperature alloys without Ru, and realizing the excellent performance of high-temperature alloys.

CN121294954APending Publication Date: 2026-01-09BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511682496.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

While the addition of Ru can suppress the precipitation of the TCP phase in existing nickel-based single-crystal superalloys, the high cost and weakening of the γ′ phase stability limit their widespread application in engineering. How to achieve both high strength and high microstructure stability without Ru has become a challenge.

Method used

By optimizing the alloy composition design and controlling the element distribution behavior to form a small-sized γ′ phase, combined with a suitable heat treatment process, the precipitation of TCP phase is suppressed and the stability of γ′ phase is improved. High-temperature alloys are prepared by using specific ratios of Cr, Co, Al, Mo, W, Ta, Re, Ti, and Hf elements and heat treatment parameters.

Benefits of technology

High strength and high microstructure stability of high-temperature alloys under Ru-free conditions were achieved, the stability of the γ′ phase was improved, and no TCP phase precipitation occurred after long-term aging, reaching the leading level at home and abroad.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a nickel-based single-crystal high-temperature alloy and a component design method and a preparation method thereof. The component design method comprises the following steps: S1, designing a plurality of button ingot polycrystalline high-temperature alloys with different component proportions; s2, aiming at all the as-cast samples of the button ingot polycrystalline high-temperature alloy, measuring the average size of a gamma'phase of each as-cast sample; s3, homogenizing all the as-cast samples of the button ingot polycrystalline high-temperature alloy, aging for 100 hours at 1100 DEG C for a long time, and measuring the volume fraction of TCP phase precipitation; and S4, the button ingot polycrystalline high-temperature alloy with the volume fraction of 0% separated out from the TCP phase is screened out, and then the button ingot polycrystalline high-temperature alloy with the minimum average size of the gamma'phase is screened out to serve as a preparation raw material of the nickel-based single-crystal high-temperature alloy. According to the alloy, no TCP phase is separated out after the alloy is aged for 1000 h at the temperature of 1100 DEG C, the stability of the high-temperature alloy is improved, and the alloy has excellent structure stability, reaches the leading level in the first three generations of alloys and exceeds part of high-generation secondary alloys containing Ru.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-temperature alloy technology, and in particular to a nickel-based single-crystal high-temperature alloy and its composition design and preparation method. Background Technology

[0002] Nickel-based single-crystal superalloys have been widely used in the aerospace field due to their excellent high-temperature comprehensive performance, especially in the manufacture of key components such as turbine blades for aero-engines, where they have shown irreplaceable advantages.

[0003] Alloying is currently the primary method for improving alloy properties, especially by adding refractory elements with high melting points and large atomic radii (such as Mo, W, and Re), which can effectively delay the evolution of the microstructure and significantly improve the high-temperature performance of the alloy. However, the addition of transition refractory elements can induce the precipitation of TCP phase. The precipitation of TCP phase not only reduces the solid solution strengthening effect, leading to a decrease in the strength of the alloy at high temperatures, but also, due to its large lattice mismatch with the matrix, forms stress concentration zones at the interface, which can easily become initiation points and propagation paths for fatigue and cracks, seriously threatening the high-temperature service stability of the material and weakening the high-temperature performance of nickel-based single-crystal superalloys. Therefore, suppressing the precipitation of TCP phase (topologically close-packed phase) in the alloy is particularly important.

[0004] In existing research, the addition of Ru is considered one of the most effective ways to suppress TCP phase precipitation in nickel-based single-crystal superalloys. However, there is currently no unified consensus on its specific mechanism of action. The main research viewpoint is that Ru can reduce the enrichment of refractory elements (such as Mo, W, Re, etc.) in the γ matrix by regulating the elemental distribution behavior between the γ matrix and the γ′ phase, thereby weakening the driving force for TCP phase formation. Secondly, Ru can inhibit the nucleation and growth process of the TCP phase, improving the microstructural stability of the alloy under high-temperature service conditions. Furthermore, the presence of Ru can increase the solid solubility of TCP-forming elements in the γ matrix, further reducing their precipitation tendency.

[0005] The applicant's previous research indicated that the core mechanism by which Ru inhibits TCP phase precipitation lies in its ability to reduce the thermal stability of the γ′ phase, increase the volume fraction of the γ matrix, and thereby dilute the concentration of TCP-forming elements in the γ matrix, thus effectively inhibiting TCP phase precipitation. However, the high cost of Ru and its side effect of weakening the stability of the γ′ phase severely limit its widespread application in engineering fields.

[0006] Therefore, in the current actual production of third-generation nickel-based single-crystal superalloys, Ru-free systems are still widely used. How to achieve both high strength and high microstructural stability in third-generation nickel-based single-crystal superalloys without relying on Ru has become an urgent problem to be solved. Summary of the Invention

[0007] This invention provides a nickel-based single-crystal high-temperature alloy and its composition design and preparation method. This method does not rely on the element Ru. Through the optimized design of the alloy composition, the precipitation of TCP phase can be effectively suppressed and the stability of γ′ phase can be improved, so that the high-temperature alloy has both high strength and high microstructure stability.

[0008] This invention provides a method for designing the composition of nickel-based single-crystal superalloys, comprising the following steps: S1. Design various button ingot polycrystalline high-temperature alloys with different composition ratios; S2. For all as-cast samples of button ingot polycrystalline superalloys, measure the size of the γ′ phase in the dendrite core and the size of the γ′ phase at the dendrite edge of each as-cast sample, and calculate the average size of the γ′ phase for each as-cast sample. S3. Homogenize all as-cast samples of button ingot polycrystalline high-temperature alloys, and then age the homogenized samples at 1100 °C for 100 h, and determine the volume fraction of TCP phase precipitation in the samples. S4. Select button-shaped polycrystalline superalloys with a TCP phase precipitation volume fraction of 0%, and then select the button-shaped polycrystalline superalloy with the smallest average size of the γ′ phase as the raw material for preparing nickel-based single crystal superalloys.

[0009] This invention proposes a third-generation nickel-based single-crystal superalloy composition design criterion and heat treatment process for forming small-sized γ′ phases by controlling the distribution behavior of alloying elements. This method effectively suppresses TCP phase precipitation and enhances the stability of the γ′ phase without relying on Ru, thereby achieving a synergistic improvement in both the γ′ phase stability and the microstructure stability of the superalloy.

[0010] According to the composition design method of the nickel-based single-crystal superalloy provided by the present invention, in step S1, the element types and their composition ranges of the currently existing third-generation nickel-based single-crystal superalloys are determined. The element types include Cr, Co, Al, Mo, W, Ta, Re, Ti, Hf, and Ni, wherein Cr, Mo, and W satisfy: Cr 2.0~5.0%, Mo 0~3.0%, and W 5.5~6.0%.

[0011] Preferably, in the currently available third-generation nickel-based single-crystal superalloys, the content of Al is 5.5-6.5%, the content of Ta is 6.0-8.0%, the content of Re is 4.5-6.5%, the content of Ti is 0-1.0%, and the content of Hf is 0-0.2%.

[0012] According to the composition design method for the nickel-based single-crystal superalloy provided by the present invention, in step S1, the contents of Al, Ta, Re, Ti, and Hf are kept constant, while the contents of Cr, Mo, and W are varied by 0.5%, and the composition ratio of each element is designed accordingly. Designing the composition within this range reduces workload and ensures rationality; preferably, the fluctuation of each element is within a range of plus or minus 0.5%.

[0013] The present invention also provides a method for preparing a nickel-based single-crystal high-temperature alloy, comprising: weighing the alloy raw materials according to the mass percentage of each component in the raw materials obtained by the composition design method described above, melting to obtain a master alloy; remelting the master alloy, casting, and then directional drawing.

[0014] According to the preparation method of the nickel-based single-crystal superalloy provided by the present invention, the melting temperature is 1680℃~1750℃, and / or the melting is carried out under vacuum conditions.

[0015] In the above scheme, by limiting the melting temperature within a reasonable range and carrying out the melting under vacuum conditions, the melting efficiency can be improved, thereby ensuring the quality of the alloy.

[0016] Furthermore, the remelting temperature is 1560~1580 ℃, the time is 5~10 min, and / or the remelting is carried out under vacuum conditions.

[0017] In the above scheme, by limiting the remelting temperature and time to a reasonable range and carrying out the remelting under vacuum conditions, the efficiency of remelting can be improved, thereby ensuring the quality of the alloy.

[0018] Furthermore, the pouring temperature is 1535~1545 ℃; and / or, the pulling rate of the directional pulling is 30~200 μm / s.

[0019] In the above scheme, by limiting the casting temperature within a reasonable range, the solidification process of the alloy can be ensured to be uniform, preventing overheating or undercooling, thereby obtaining a high-quality alloy. Limiting the pulling rate of directional pulling within a reasonable range is beneficial for controlling the alloy's solidification structure and optimizing its properties.

[0020] According to the preparation method of the nickel-based single crystal superalloy provided by the present invention, the preparation method further includes a heat treatment step of the single crystal rod obtained by directional drawing, the heat treatment including solution treatment, the solution treatment including: first heating to 1345 ℃, holding at that temperature for 8 h, then heating to 1375 ℃, and holding at that temperature for 4 h.

[0021] Preferably, the heating rate during the solution treatment is 2 to 5 °C / min.

[0022] According to the preparation method of the nickel-based single-crystal superalloy provided by the present invention, the heat treatment further includes an aging treatment after solution treatment. The aging treatment includes first heating to 1160 °C, holding at that temperature for 4 h, and then air cooling to room temperature; then heating to 870 °C, holding at that temperature for 24 h, and then air cooling to room temperature; and finally heating to 760 °C, holding at that temperature for 24 h, and then air cooling to room temperature.

[0023] Preferably, the heating rate during the aging treatment is 2 to 5 °C / min.

[0024] According to the preparation method of the nickel-based single-crystal superalloy provided by the present invention, the heat treatment is carried out under an argon atmosphere.

[0025] The present invention also provides a nickel-based single-crystal superalloy, which is designed by the design method described above or prepared by the preparation method described above.

[0026] According to the nickel-based single-crystal superalloy provided by the present invention, the nickel-based single-crystal superalloy comprises, by mass percentage: Cr 2.5±0.5%, Co 10.0±0.5%, Al 5.0±0.5%, Mo 1.0±0.5%, W 6.0±0.5%, Ta 7.5±0.5%, Re 6.0±0.5%, Ti 0.5±0.2%, Hf 0.1±0.02%, with the remainder being Ni and unavoidable impurities.

[0027] The composition design criteria and heat treatment process of this invention can achieve both high strength and high microstructure stability in high-temperature alloys. The γ′ phase in the alloy microstructure after heat treatment has good cubicity and stability, and no TCP phase precipitation occurred after aging treatment at 1100 °C for 1000 h, reaching the leading level of similar alloys at home and abroad.

[0028] The beneficial effects of the nickel-based single-crystal superalloy, its composition design method, and its preparation method provided by this invention are as follows: 1. This invention, through the optimized design of the alloy, can effectively suppress TCP phase precipitation and improve the stability of the γ′ phase without relying on the Ru element, thereby achieving a synergistic effect of high strength and high microstructure stability in high-temperature alloys. Combined with a suitable heat treatment process, the alloy exhibits excellent microstructure stability. No TCP phase precipitation occurred after aging treatment at 1100 ℃ for 1000 h, reaching the leading level of similar alloys at home and abroad.

[0029] 2. This invention essentially eliminates residual segregation through solution treatment and ensures the size and cubicity of the γ′ phase through aging treatment. After heat treatment, the γ′ phase of the high-temperature alloy has a small size and exhibits good stability during long-term aging. After aging for 1000 hours, the γ′ phase of the heat-treated alloy did not undergo rafting, demonstrating good microstructural stability. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0031] Figure 1 This is a statistical result of the average size of the γ′ phase and the volume fraction of TCP phase precipitation in the as-cast microstructure of the 10 groups of button ingot polycrystalline high-temperature alloys in Example 1 after homogenization and long-term aging at 1100 °C for 100 h.

[0032] Figure 2 This is a low-magnification microstructure diagram of the as-cast alloy prepared in Example 2.

[0033] Figure 3 This is a low-magnification microstructure diagram of the alloy after solution treatment in Example 3.

[0034] Figure 4 This is a low-magnification microstructure diagram of the alloy after solution treatment in Comparative Example 1.

[0035] Figure 5 This is a low-magnification microstructure diagram of the alloy after solution treatment in Comparative Example 2.

[0036] Figure 6 This is a γ / γ′ microstructure diagram of the alloy after one aging treatment in Example 4.

[0037] Figure 7 This is the γ / γ′ microstructure of the alloy in Comparative Example 3 after one aging treatment.

[0038] Figure 8 This is the γ / γ′ microstructure of the alloy in Comparative Example 4 after one aging treatment.

[0039] Figure 9 This is a microstructure diagram of the γ / γ′ structure of the alloy prepared in Example 5 after final heat treatment.

[0040] Figure 10 This is a low-magnification microstructure of the alloy prepared in Example 5 after heat treatment and long-term aging for 1000 h.

[0041] Figure 11 The image shows the γ / γ′ microstructure of the alloy prepared in Example 5 after heat treatment and long-term aging for 1000 h.

[0042] Figure 12 This is a comparison of the microstructure stability of the alloy prepared in Example 5 with nickel-based single-crystal high-temperature alloys from home and abroad. Detailed Implementation

[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0044] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.

[0045] Example 1 This embodiment provides a method for designing the composition of a nickel-based single-crystal superalloy. The nickel-based single-crystal superalloy to be designed is a third-generation nickel-based single-crystal superalloy, and the elements are selected from Cr, Co, Al, Mo, W, Ta, Re, Ti, Hf, and Ni. The method includes the following steps: S1. With the contents of Re, Co, Ta, Ti, Al and Hf in the third-generation nickel-based single-crystal superalloy fixed at 6.0%, 10.0%, 7.5%, 0.5%, 5.0% and 0.1%, respectively, within the range of Cr: 2.0-5.0%, Mo: 0-3.0%, W: 5.5-6.0%, and using 0.5% as the element content variable, 10 button-shaped polycrystalline superalloys with different composition ratios were designed (numbered sequentially as alloy 1 to 10); the composition ratios of alloys 1 to 10 are shown in Table 1 below.

[0046] Table 1 Composition ratios of alloys 1-10 alloy Re Cr Co W Mo Ta Ti Al other 1 6.0 3.0 10.0 6.0 2.0 7.5 0.5 5.0 0.1Hf 2 6.0 3.0 10.0 6.0 1.5 7.5 0.5 5.0 0.1Hf 3 6.0 3.0 10.0 6.5 1.5 7.5 0.5 5.0 0.1Hf 4 6.0 2.5 10.0 6.0 1.0 7.5 0.5 5.0 0.1Hf 5 6.0 3.0 10.0 6.5 1.0 7.5 0.5 5.0 0.1Hf 6 6.0 3.0 10.0 7.5 1.0 7.5 0.5 5.0 0.1Hf 7 6.0 2.5 10.0 6.0 1.5 7.5 0.5 5.0 0.1Hf 8 6.0 3.0 10.0 6.0 1.0 7.5 0.5 5.0 0.1Hf 9 6.0 2.5 10.0 6.5 1.0 7.5 0.5 5.0 0.1Hf 10 6.0 3.0 10.0 7.0 1.0 7.5 0.5 5.0 0.1Hf S2. Place the button ingot polycrystalline superalloy in a vacuum induction melting furnace, melt it uniformly under high vacuum conditions, and then pour it into a preheated mold cavity at 1540℃ to obtain a cast sample of button ingot polycrystalline superalloy with uniform composition. For all the cast samples of button ingot polycrystalline superalloy, measure the size of the γ′ phase in the dendrite core and the size of the γ′ phase at the dendrite edge of each cast sample, and count the average size of the γ′ phase of each cast sample.

[0047] S3. All as-cast samples of the button ingot polycrystalline superalloy were homogenized. The homogenization process was as follows: the furnace chamber was heated to 1340 ℃ at a heating rate of 5 ℃ / min, held for 10 h, and then the homogenized samples were aged at 1100 ℃ for 100 h. The volume fraction of TCP phase precipitation in the samples was then measured. The results of the average size of the γ′ phase and the volume fraction of TCP are as follows. Figure 1 As shown in Table 2.

[0048] Table 2. Average size and TCP volume fraction of γ′ phase in alloys 1–10 Alloy type Average size of γ′ phase (nm) TCP volume fraction (%) Alloy 1 117.00 0.83 Alloy 2 129.50 1.07 Alloy 3 115.50 2.75 Alloy 4 65.50 0.00 Alloy 5 134.50 1.83 Alloy 6 186.00 2.18 Alloy 7 74.50 0.00 Alloy 8 72.50 0.00 Alloy 9 102.50 1.76 Alloy 10 116.50 1.22 S4. First, select several button-shaped polycrystalline superalloys (alloys 4, 7, and 8) that do not precipitate TCP phase (the volume fraction of TCP phase precipitation is 0%). Then, select the group of button-shaped polycrystalline superalloys with the smallest average size of γ′ phase. Specifically, as shown in Table 2, although alloys 4, 7, and 8 do not precipitate TCP phase after 100 h of long-term aging, alloy 4 has the smallest average γ′ phase size of 65.5 nm. Therefore, alloy 4 is used as the raw material for the preparation of high-stability third-generation nickel-based single-crystal superalloys.

[0049] Example 2 Single-crystal test rods were prepared using the composition of Alloy 4 from Example 1 as the nominal composition. The prepared raw materials were placed in a vacuum induction melting furnace for melting at a temperature of 1700 °C. After obtaining the molten metal, the molten metal was cast to form a nickel-based single-crystal high-temperature alloy master alloy.

[0050] The nickel-based single-crystal superalloy master alloy obtained by vacuum melting was placed in a crucible of a vacuum induction directional solidification furnace for remelting. During this process, the refining temperature of the nickel-based single-crystal superalloy master alloy was 1570 °C, and the time was 10 min.

[0051] Molten metal was poured into a single-crystal test rod mold, and then the mold was pulled downwards to prepare a nickel-based single-crystal superalloy rod. The pouring temperature was 1540 ℃, and the pulling rate after pouring was 100 μm / s. The single-crystal test rod mold was then directionally pulled out of the heater, and cooled at the bottom using a water-cooling pan. This yielded a cast nickel-based single-crystal superalloy rod with dimensions of Φ16 mm × 150 mm.

[0052] Furthermore, the as-cast microstructure of the new alloy was characterized, among which... Figure 2 The image shows the dendritic structure of the new alloy, with the inset showing the γ′ phase between the dendrites and dendrites. It can be seen that the as-cast structure of the alloy exhibits a distinct dendritic structure, which is cross-shaped. A relatively darker eutectic structure appears between the dendrites. Furthermore, due to compositional inhomogeneity, the γ′ phase at the dendrites is significantly larger than that at the dendrites.

[0053] Example 3 This embodiment describes the solution treatment of the as-cast nickel-based single-crystal superalloy rod prepared in Example 2 to obtain a solution-treated nickel-based single-crystal superalloy test rod. The solution treatment process is as follows: starting from an initial temperature of 20 ℃ (room temperature), the furnace chamber is heated to 1345 ℃ at a heating rate of 5 ℃ / min and held for 8 h, then heated to 1375 ℃ at a heating rate of 5 ℃ / min and held for 4 h. After the heating is completed, the test rod is removed and air-cooled to room temperature to obtain the solution-treated nickel-based single-crystal superalloy test rod.

[0054] Furthermore, the solid solution microstructure of the alloy in Example 3 was characterized, such as... Figure 3 As shown in the figure, the eutectic structure and segregation have been eliminated, and the structure is uniform.

[0055] Comparative Example 1 The difference between this comparative example and Example 3 is that the solution treatment process is as follows: Starting from an initial temperature of 20 ℃ (room temperature), the furnace chamber was heated to 1345 ℃ at a heating rate of 5 ℃ / min and held for 8 h. Subsequently, the temperature was increased to 1370 ℃ at a rate of 5 ℃ / min and held for 4 h. After the heating was completed, the test bar was removed and air-cooled to room temperature to obtain a solution-treated nickel-based single crystal superalloy test bar.

[0056] Furthermore, the solid solution microstructure of the alloy in Comparative Example 1 was characterized, such as... Figure 4 As shown, residual segregation still exists between the dendrite trunk and the dendrites.

[0057] Comparative Example 2 The difference from Example 3 is that the solution treatment is as follows: Starting from an initial temperature of 20 °C (room temperature), the furnace chamber was heated to 1345 °C at a heating rate of 5 °C / min and held for 8 hours. Subsequently, the temperature was increased to 1380 °C at a rate of 5 °C / min and held for 4 hours. After the heating was completed, the test bar was removed and air-cooled to room temperature to obtain a solution-treated nickel-based single-crystal superalloy test bar.

[0058] Furthermore, the solid solution microstructure of the alloy in Comparative Example 2 was characterized, such as... Figure 5 As shown in the figure, the eutectic structure and segregation are eliminated, but compared with Example 3, the number of micropores increases significantly after solution treatment. Considering the above factors, Example 3 is determined to be the optimal solution treatment process.

[0059] Example 4 In this embodiment, the alloy prepared in Example 3 after solution treatment is subjected to a first aging process, as follows: The first aging stage begins at an initial temperature of 20 ℃ (room temperature), and the furnace chamber is heated to 1160 ℃ at a heating rate of 5 ℃ / min, and held at that temperature for 4 h. After the heating is completed, the test bar is removed and air-cooled to room temperature.

[0060] Furthermore, the microstructure of the alloy in Example 4 after a single aging treatment was characterized, such as... Figure 6 As shown in the figure, the γ′ phase has better cubicity.

[0061] Comparative Example 3 The difference between this comparative example and Example 4 is that, starting from an initial temperature of 20 ℃ (room temperature), the furnace cavity was heated to 1140 ℃ at a heating rate of 5 ℃ / min and held at that temperature for 4 h. After the heating was completed, the test bar was removed and air-cooled to room temperature.

[0062] Furthermore, the microstructure of the alloy in Comparative Example 3 after a single aging treatment was characterized, such as... Figure 7 As shown in the figure, the γ′ phase has poor cubicity.

[0063] Comparative Example 4 The difference between this comparative example and Example 4 is that the first aging stage starts from an initial temperature of 20 ℃ (room temperature), and the furnace cavity is heated to 1180 ℃ at a heating rate of 5 ℃ / min, and held at that temperature for 4 h. After the heating is completed, the test bar is removed and air-cooled to room temperature.

[0064] Furthermore, the microstructure of the alloy in Comparative Example 4 after a single aging treatment was characterized, such as... Figure 8 As shown in the figure, the γ′ phase size is larger compared to Example 4. Considering the above factors, Example 4 is determined to be the optimal single-stage aging process.

[0065] Example 5 In this embodiment, the alloy prepared in Example 4 after a single aging treatment is subjected to a second and third aging process. Specifically, starting from an initial temperature of 20 ℃ (room temperature), the furnace cavity is heated to 870 ℃ at a heating rate of 5 ℃ / min and held for 24 h. Then, starting from an initial temperature of 20 ℃ (room temperature), the furnace cavity is heated to 760 ℃ at a heating rate of 5 ℃ / min and held for 24 h to obtain an aged nickel-based single crystal high-temperature alloy test bar.

[0066] The final image of the γ / γ′ microstructure of the new alloy after complete heat treatment is shown below. Figure 9 As shown in the figure, the γ′ phase has a higher cubicity compared to the first aging.

[0067] Subsequently, a long-term aging test was conducted at 1100 ℃, and the results after 1000 h were as follows. Figure 10 and Figure 11 As shown, the γ′ phase size gradually increases during this process, following a ripening mechanism. No TCP phase precipitation was observed in the microstructure, indicating excellent microstructural stability.

[0068] Figure 12 This section compares the microstructure stability of the alloy obtained in Example 5 with that of three generations of nickel-based single-crystal superalloys from both domestic and international sources. The results show that the microstructure stability of the new alloy in Example 5 is at a leading level among the first three generations of alloys and surpasses that of some higher-generation Ru-containing alloys.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for designing the composition of a nickel-based single-crystal superalloy, characterized in that, Includes the following steps: S1. Design various button ingot polycrystalline high-temperature alloys with different composition ratios; S2. For all as-cast samples of button ingot polycrystalline superalloys, determine the average size of the γ′ phase for each as-cast sample; S3. Homogenize all as-cast samples of button ingot polycrystalline high-temperature alloys, and then age the homogenized samples at 1100 °C for 100 h, and determine the volume fraction of TCP phase precipitation in the samples. S4. Select button-shaped polycrystalline superalloys with a TCP phase precipitation volume fraction of 0%, and then select the button-shaped polycrystalline superalloy with the smallest average size of the γ′ phase as the raw material for preparing nickel-based single crystal superalloys.

2. The composition design method for nickel-based single-crystal superalloys according to claim 1, characterized in that, S1 identifies the element types and composition ranges of the currently existing third-generation nickel-based single-crystal superalloys. The element types include Cr, Co, Al, Mo, W, Ta, Re, Ti, Hf, and Ni, wherein Cr, Mo, and W satisfy the following: Cr 2.0–5.0%, Mo 0–3.0%, and W 5.5–6.0%. Preferably, in the currently available third-generation nickel-based single-crystal superalloys, the content of Al is 5.5-6.5%, the content of Ta is 6.0-8.0%, the content of Re is 4.5-6.5%, the content of Ti is 0-1.0%, and the content of Hf is 0-0.2%.

3. The composition design method for nickel-based single-crystal superalloys according to claim 2, characterized in that, In step S1, the contents of Al, Ta, Re, Ti and Hf are kept constant, while the contents of Cr, Mo and W are varied by 0.5% to design the composition ratio of each element.

4. A method for preparing a nickel-based single-crystal superalloy, characterized in that, include: Weigh the alloy raw materials according to the mass percentage of each component in the raw materials prepared by the composition design method according to any one of claims 1-3, and melt them to obtain the master alloy; remelt the master alloy, cast it, and then pull it in a specific direction.

5. The method for preparing nickel-based single-crystal superalloys according to claim 4, characterized in that, The melting temperature is 1680℃~1750℃; And / or, the melting is carried out under vacuum conditions; And / or, the remelting temperature is 1560~1580 ℃ and the time is 5~10 min; And / or, the remelting is carried out under vacuum conditions; And / or, the pouring temperature is 1535~1545 ℃; And / or, the pulling rate of the directional pulling is 30~200 μm / s.

6. The method for preparing nickel-based single-crystal superalloys according to claim 4, characterized in that, The preparation method further includes a heat treatment step on the single crystal rod obtained by the directional pulling, the heat treatment including a solution treatment, the solution treatment including: first heating to 1345 ℃, holding for 8 h, then heating to 1375 ℃, holding for 4 h; Preferably, the heating rate during the solution treatment is 2 to 5 °C / min.

7. The method for preparing a nickel-based single-crystal superalloy according to claim 6, characterized in that, The heat treatment also includes an aging treatment after solution treatment. The aging treatment includes first heating to 1160 °C, holding for 4 h, and air cooling to room temperature; then heating to 870 °C, holding for 24 h, and air cooling to room temperature; and finally heating to 760 °C, holding for 24 h, and air cooling to room temperature. Preferably, the heating rate during the aging treatment is 2 to 5 °C / min.

8. The method for preparing a nickel-based single-crystal superalloy according to any one of claims 4-7, characterized in that, The heat treatment was performed under an argon atmosphere.

9. A nickel-based single-crystal superalloy, characterized in that, It is designed using the design method described in any one of claims 1-3 or prepared using the preparation method described in any one of claims 4-8.

10. The nickel-based single-crystal superalloy according to claim 9, characterized in that, The nickel-based single-crystal superalloy comprises, by mass percentage: Cr 2.5±0.5%, Co 10.0±0.5%, Al 5.0±0.5%, Mo 1.0±0.5%, W 6.0±0.5%, Ta 7.5±0.5%, Re 6.0±0.5%, Ti 0.5±0.2%, Hf 0.1±0.02%, with the remainder being Ni and unavoidable impurities.